Cak Nun dan Esai Sastrawinya dalam Perspektif Kriminologi - Ahmadi, Anas (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2019)
Criminology studies are related to crime studies. Criminology studies attract many academics because these studies are dynamic and can be included in various study areas, one of them is the study of criminology that is included in the study of literature. As a form of creation of the author, literature also raises things related to criminology. In this research, criminology is presented in the Indonesian literary essay. In this case, Indonesian literature is limited to Emha Ainun Najib's work in the form of literary essays. This qualitative-interpretive research study uses data sources from Slilit Sang Kiai (2013); Arus Bawah (2015); and Gelandangan di Kampung Sendiri (2015). The theory used in this research is criminology theory. Based on the analysis, it was concluded that Cak Nun as a cultural figure presented crimes in his literary essay, which is as follows. First, based on an analysis of the criminological context, the forms of crime in Emha Ainun Najib's work include, among others (1) crime of environmental destruction; (2) questionnaire manipulation crime; (3) murder crime; (4) crime of prostitution; and (5) white-collar crimes. Secondly, the tendency of crime to emerge in the work of Emha Ainun Najid through her three works, which is more towards the crime of the government to the people. Second, the tendency of crime that is raised in the work of Emha Ainun Najib through his three works are more directed at government crime against the people